Washington versus Beijing consensus: Is the Beijing consensus a suitable model for attaining Angola's development objectives - Mazibuko, Jefrey (My University, 2014)
The period after the end of the Cold War the early 1990s, when number of academics would continuously label the United States of America (USA), France and the United Kingdom (UK) as the only external supremacies to have extensive interests in Sub-Saharan African countries such as Angola with the use of the Washington Consensus, has contemporary been threatened by the new African economic dependency on China through the Beijing consensus (Frieden, 2000, 14). Over the course of the past ten years or so, the People’s Republic of China (PRC) has established itself as a progressively prevailing player across Sub-Saharan Africa. Academics have consequently argued that China in Africa has been a theme widely discussed lately and one of the questions that centre’s around this discussion; is the Beijing Consensus a suitable model for achieving Angola’s development objectives as compared to earlier Western attempts through Washington Consensus?